Sejarah Gerakan Islam/ Tentara Islam Indonesia dengan Perspektif Hukum Responsif - Saskia Nursukma Andriliani; Taufiqurrohman Syahuri (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The DI/TII social movement, which began on August 7, 1949, emerged as a result of socio-political tensions, particularly resistance to the Reorganization and Rationalization (Rera) policy. This movement aimed to establish an Islamic state in Indonesia and arose as a reaction to government policies perceived as inconsistent with Islamic principles. Discontent among former TNI soldiers and local militias due to the Rera policy fueled the movement, with many of these disillusioned individuals joining DI/TII. On February 10–11, 1948, Sekarmadji Maridjan Kartosuwiryo and Raden Oni organized a conference of Islamic leaders, during which the idea of forming the Islamic State of Indonesia (Negara Islam Indonesia, NII) was introduced. Kartosuwiryo declared himself the Grand Imam of the Islamic State of Indonesia. The widespread and massive expansion of this movement increasingly disrupted society, as it involved acts of extortion and armed resistance, creating unrest and opposition among the population. In response, the Indonesian government adopted a responsive legal approach, reflected in measures such as the enactment of the Emergency Law of 1949 and the re-adoption of the 1945 Constitution, which included restrictions in Article 28J(2). Various efforts were undertaken to address the situation, including the deployment of military operations to suppress the rebellion and restore stability.